2006
DOI: 10.1590/s1516-31802006000300009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of free circulating Epstein-Barr virus DNA in plasma of patients with Hodgkin’s disease

Abstract: EBV DNA was present in 91% of patients with EBV-associated Hodgkins disease, and in all patients with HIV-associated Hodgkins disease. EBV DNA prevalence was higher in patients with advanced disease, irrespective of HIV status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…8 Others have reported an association between detectable plasma EBV-DNA and higher stage disease. 10 A recent study of patients with newly diagnosed or relapsed HL found pretreatment plasma EBV-DNA to be associated with EBV status by EBER-ISH and noted that plasma EBV-DNA levels declined with treatment. 11 Herein, we examine the relationship in HL between plasma EBV-DNA measurement and EBV tumor status and explore the utility of plasma EBV-DNA as a prognostic marker at diagnosis and 6-month follow-up.…”
Section: Epstein-barr Virus (Ebv) Is a Gammaherpesvirus Present Inmentioning
confidence: 99%
“…8 Others have reported an association between detectable plasma EBV-DNA and higher stage disease. 10 A recent study of patients with newly diagnosed or relapsed HL found pretreatment plasma EBV-DNA to be associated with EBV status by EBER-ISH and noted that plasma EBV-DNA levels declined with treatment. 11 Herein, we examine the relationship in HL between plasma EBV-DNA measurement and EBV tumor status and explore the utility of plasma EBV-DNA as a prognostic marker at diagnosis and 6-month follow-up.…”
Section: Epstein-barr Virus (Ebv) Is a Gammaherpesvirus Present Inmentioning
confidence: 99%
“…Their real-time quantitative PCR resulted in a lower overall positivity rate: 69% (18/26) samples from EBV-positive HL and 10% (2/20) samples from EBV-negative cases were positive. Using conventional PCR, Musacchio et al [3] observed similar results: 91% (10/11) of EBV-positive HL patients were EBV-DNA-positive in plasma, and 16% (3/19) of cases without LMP1 had detectable free circulating EBV-DNA.…”
mentioning
confidence: 71%
“…Latent EBV genomes are found in the malignant Reed-Sternberg/Hodgkin cells in approximately 30-50% of patients with HL in Western countries. Several studies have reported presence of EBV-DNA in the blood of patients with EBV-positive HL [3] . However, the significance of EBV-DNA monitoring is debated.…”
mentioning
confidence: 99%
“…Patients with untreated EBV(+) lymphomas or EBV-associated hemophagocytic lymphohistiocytosis (EBV-HLH) consistently have EBV DNA detected in plasma, often at high copy number (Martelius et al 2010;Lei et al 2001Lei et al , 2002Kanakry et al 2013;Musacchio et al 2006;Donati et al 2006;Gallagher et al 1999;Elazary et al 2007;Teramura et al 2002;Morishima et al 2014;Suwiwat et al 2007;Beutel et al 2009). Across EBV(+) lymphomas of B-, T-, and NK-cell lineage, EBV DNA has been demonstrated to be detectable in the plasma prior to therapy in the majority of patients and to be markedly elevated in many (Machado et al 2010;Au et al 2004;Kanakry et al 2013).…”
Section: Ebv(+) Lymphomas and Lymphoproliferative Disordersmentioning
confidence: 99%